Hadiths of Traveling Fasting of Ignorance in The Al-Kafi Book Study and Analysis - Hassan A'athib, Lubna (Journal of College of Education, 2022)
Fasting is one of the important pillars that God almighty has imposed on a Muslim, and his conversion to Islam is not complete without it, but some people are permitted to break their fast for an excuse such as travelling. The traveler has been permitted to break his fast on the condition that the travel requires shortening the prayers, i.e. the long journey, because of the hardship that leads to breaking the fast. He must make it up during the days of residence, but if he was ignorant of the ruling on breaking the fast while traveling, his fast is valid.